Determining hemodynamic significance of patent ductus arteriosus using echocardiographic data prognostic tables - D.A. Kulikova; I.N. Safonova; L.I. Chumak; I.N. Poddubnaya; O.S. Protsenko; D.G. Dotsenko (Medičnì Perspektivi)
The paper presents an analysis of echocardiographic data of patients with PDA having different hemodynamic significance. Presently, the concept of “degree of hemodynamic significance” remains controversial. Criteria for determining the hemodynamic significance of PDA in term infants are not described. In our work, we used a classification of three degrees of hemodynamic significance: non-hemodynamically significant PDA – insignificant, moderately hemodynamically significant – moderately significant and large PDA – hemodynamically significant PDA. Aim – to work out an algorithm for determining the degree of PDA hemodynamic significance for prediction of its further development. The study involved children under 18 years old (80% of them ‒ children under 3 years old) who were examined in the cardiac surgery department of the SI “IGUS n.a.V.T. Zaytsev NAMS of Ukraine” during 2013-2017 yy. Gestational age (from 37 weeks), the presence of left to right PDA shunt, absence of a ASD shunt and other congenital heart defects served as enrollment criteria for the trial. Two prognostic tables were formed with the main criteria for determining hemodynamic significance of PDA by the sum of the signs according to gradations (insignificant, moderately significant and hemodynamically significant) as an outcome of the trial. Based on the determination of the main and additional criteria of hemodynamic significance and the strength of their influence, a diagnostic algorithm is formed for a patient with PDA with the possibility of predicting a further clinical scenario. For determination of hemodynamic significance, an increase in pulmonary gradient with an information index of 1.135 and a prognostic factor of +5.90/-1.75 were dominant, while the left ventricular dilatation located from the A4C with an informational index of 1.020 and a prognostic coefficient of +3.69/-2.50 dominated in determining the degree of hemodynamic significance in the presence of secondary changes. The proposed mechanism for determining the level of hemodynamic significance of PDA for children with borderline changes will predict more precisely the development of the disease, determine the patient’s observation tactics and regulate the decision-making process of surgical intervention.